2019
DOI: 10.1038/s41598-019-49056-6
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 increases viral burden and promotes HIV-1 latency in primary differentiated human bronchial epithelial cells

Abstract: Combination antiretroviral therapy (cART) has increased the life expectancy of HIV patients. However, the incidence of non-AIDS associated lung comorbidities, such as COPD and asthma, and that of opportunistic lung infections have become more common among this population. HIV proteins secreted by the anatomical HIV reservoirs can have both autocrine and paracrine effects contributing to the HIV-associated comorbidities. HIV has been recovered from cell-free bronchoalveolar lavage fluid, alveolar macrophages, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…"Glycosaminoglycan biosynthesis-heparan sulfate/heparin" was here related to miRs 3934-3. Heparan sulfate proteoglycans have previously been identified to provide the binding sites for SARS-CoV-2 invasion at the early attachment phase [76]. Furthermore, human coronavirus NL63 has been shown to utilise heparan sulfate proteoglycans for target cell attachment [77].…”
Section: Mir-3934-3pmentioning
confidence: 99%
“…"Glycosaminoglycan biosynthesis-heparan sulfate/heparin" was here related to miRs 3934-3. Heparan sulfate proteoglycans have previously been identified to provide the binding sites for SARS-CoV-2 invasion at the early attachment phase [76]. Furthermore, human coronavirus NL63 has been shown to utilise heparan sulfate proteoglycans for target cell attachment [77].…”
Section: Mir-3934-3pmentioning
confidence: 99%
“…Tobacco smoking is the principal risk factor for COPD. Cigarette smokers and COPD patients demonstrate chronic induction of TGF-β signaling 98, 99, 100, 101, 102. We have demonstrated that TGF-β upregulates miR-145-5p in bronchial epithelial cells 100 .…”
Section: Main Textmentioning
confidence: 75%
“…miR-5197 is also related to the KEGG morphine addiction pathway, which is linked to enhanced HIV-1 infection, HCV replicon expression, the reduced clearance of pulmonary influenza virus infection in rats, and increased SAIDS in rhesus monkeys [ 52 , 53 , 54 , 55 , 56 , 57 ]. miR-5197 furthermore influences the metabolism of xenobiotics by cytochrome P450 mechanisms and the TGF-β signaling pathway, which is associated with viral entry and HIV infection [ 58 ] and is strongly linked to both pulmonary and cardiovascular diseases [ 59 , 60 , 61 ]. Furthermore, miR-5197 is related to p53 regulatory pathways and cancers, ubiquitin-related proteolysis, and molecular and cellular GO pathways linked to nucleic acid binding and to nuclear and organelle function ( Figure S2 ) (please see further in depth discussion on these pathways in Ref.…”
Section: Discussionmentioning
confidence: 99%